(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article is presents a comparative analysis of important reforms in the education system of Uzbekistan. are given is the names and forms of the introduced innovations, which are adapted for the Republic of Uzbekistan. Also, problems in the education system are indicated and solutions are proposed to eliminate them.